Control of Selenoprotein F Translation in Prostate Cancer. (29th May 2020) - Kadkol, Shrinidhi; Hong, Lenny; Diamond, Alan
Abstract: Objectives: Selenoprotein F (SELENOF) is a selenocysteine-containing protein whose levels are responsive to selenium availability and are often lower in prostate cancer (PCa) compared to benign regions. Lowering SELENOF levels in cultured, non-transformed prostate cells results in these cells gaining a transformed phenotype, indicating that SELENOF may function as a tumor suppressor. The reasons for the loss of SELENOF in PCa remain unknown. SELENOF translation requires a se lenoc ysteine i nsertion s equence (SECIS), a stem-loop structure within the 3'– untranslated region (UTR) of the SELENOF mRNA. The objective of this study is to determine if SECIS-mediated UGA recoding is impeded in PCa, resulting in lower SELENOF protein levels. Methods: In order to establish a cell model for the decrease in SELENOF levels, SELENOF levels were determined by western blot analysis of protein from PC3 PCa cells and RWPE-1 immortalized but not tumorigenic prostate cells. SELENOF mRNA levels in each of these cell lines was subsequently determined by RT-qPCR. In order to determine the efficiency of UGA readthrough in PC3 and RWPE-1 cells, reporter constructs were generated in which an in-frame UGA was introduced into the open reading frame of firefly luciferase by in-vitro mutagenesis and the constructs included portions of the SELENOF 3'-UTR required for UGA recoding. Results: SELENOF levels were 18 times lower in PC3 cells compared to the RWPE-1 cells, while mRNA levels were similar between the two. Using the generated reporter constructs, differences in UGA recoding efficiency in PC3 and RWPE-1 cells were apparent, as were unexpected contributions of portions of the 3'UTR sequences to UGA readthrough efficiency. Conclusions: Differing levels of SELENOF seen in prostate tissues were recapitulated in a cell culture model, with there being significantly less protein in PC3 cells compared to RWPE-1 cells, without a comparable difference in mRNA. Changes in SELENOF levels due to altered regulation of UGA recoding may be a significant event in PCa progression. Funding Sources: This work was supported by the University of Illinois at Chicago Liberal Arts and Sciences Undergraduate Research Initiative (LASURI) to SK and Department of Defense Prostate Cancer Research Program to AMD.